2017
DOI: 10.5539/jel.v6n4p181
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Teachers’ Educational Beliefs and Their Views about the Principles of Critical Pedagogy

Abstract: The main idea behind this research is to determine prospective teachers’ educational beliefs and their views about critical pedagogy. Therefore, the purpose of this research is to analyze the relationship between prospective teachers’ educational beliefs and their views about critical pedagogy. In this study, “Educational Beliefs Scale” is used with the “Principals of Critical Pedagogy Scale”. Based on the Educational Beliefs Scale, five theories on educational philosophy including: Perennialism, Essentialism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…Suprisingly, it was found that there is a relationship between perennialism and reconstructivism and this relationship could be explained in some ways. In the study by Kaya and Kaya (2017), it was revealed that there is a relationship between perennialism, essentialism and reconstructivism. They stated that they are correlated with the principles of critical pedagogy and the functions of the schools.…”
Section: Discussionmentioning
confidence: 99%
“…Suprisingly, it was found that there is a relationship between perennialism and reconstructivism and this relationship could be explained in some ways. In the study by Kaya and Kaya (2017), it was revealed that there is a relationship between perennialism, essentialism and reconstructivism. They stated that they are correlated with the principles of critical pedagogy and the functions of the schools.…”
Section: Discussionmentioning
confidence: 99%
“…Freire (2001) defined critical pedagogy as a critical approach to education, highlighting the importance of engaging learners actively in their learning process, and developing their own opinions and positions. Kaya and Kaya (2017;p. 182) expound that critical pedagogy is a tool to "address the problem of education and the education system itself."…”
Section: Discussionmentioning
confidence: 99%
“…Eğitim alanında yer alan farklı yaklaşımlara yönelik Türkiye'de sınırlı sayıda araştırma yapılmıştır. Bu araştırmaların ise daha çok eleştirel pedagoji, alternatif okullar, Reggio Emilia ve Montessori yaklaşımlarına yönelik olduğu görülmüştür (Yılmaz & Altınkurt, 2011;Şahin Sak, 2014;Aslan & Kozikoğlu, 2015;Sarıgöz & Özkara, 2015;Memduhoğlu, Mazlum & Alav, 2015;Turhan Türkkan & Boran Şenocak, 2021;Birinci, 2017;Kaya & Kaya, 2017;Schreglmann, 2019). Daha çok bu konulara yönelik araştırmalar yapılmasının nedeninin ise, geleneksel yaklaşımların dışındaki yaklaşımlar denilince alternatif okulların ele alınması olabilir.…”
Section: Introductionunclassified